Fifty years of Teikei: the evolution of the movement’s ten principles and its impact on alternative food initiatives in Japan - Kondo, Chika; Zollet, Simona; Kobayashi, Mai; Yamamoto, Nami (Frontiers in Sustainable Food Systems, 2024)
Japan’s teikei movement, recognized as a source of inspiration for Community Supported Agriculture (CSA) in Western countries, is now entering its fifth decade. Built upon trust and shared values, teikei relies on mutually supportive relationships between organic producers and consumers. The movement’s commitments were originally articulated through the ten principles of teikei, which offer a roadmap to create food systems based on solidarity principles going beyond market transactions. Despite a decline in numbers, teikei groups continue to operate in the midst of societal shifts impacting food practices and consumption patterns. These changes have affected the implementation of the ten principles and power dynamics between producers and consumers. This research investigates how such shifts have affected the development of alternative food systems in Japan, the evolution of teikei as a social movement, and the tensions that arise from contrasting notions of agri-food system alterity rooted in decommodified relationships versus market-based transactions. We employ the ten principles as a framework to investigate the transformations of some representative teikei groups over time, and identify three types of shifts: relational, operational, and ideological. These shifts demonstrate how teikei actors have worked twards building sustainable agri-food systems through alternative market relations. The shifts also underscore the fluid and situated nature of agri-food system alterity within historical, geographical, and relational spaces. The current variations of teikei configurations and the progressive diversification of approaches to address the challenges of upholding the original principles demonstrate the movement’s adaptability over time. However, they also demonstrate the necessity to strike a compromise between conflicting needs.The development of the teikei movement is not only important from an historical and geographically-situated perspective, but also as an evolving experiment in the potential and challenges of active food citizenship. The democratic decision-making processes embedded within teikei principles and practices offer a valuable model for understanding how individuals enact their food citizenship and contribute to ongoing transformation of the agri-food system. Simultaneously, these shifts also serve as a warning about the erosion of democratic priniciples by conventionalization and neoliberalization, and the assumptions made during the process of building alternative agri-food systems, such as gendered labor.